THE PERFORMANCE PATTERN OF TEACHERS’ SPEAKING AT PRIME ONE SCHOOL: AN ANTHROPOLINGUISTIC APPROACH - Nenni Triana Sinaga; Febrika Dwi Lestari; Sarma Panggabean; Zubilezer Sihite; Cia Tesalonika Munthe (TELL - US JOURNAL, 2026)
The teachers’ speaking performance pattern at Prime One School is a manifestation of the legitimacy of teachers’ speaking performance at the international school. The applied teaching performance patterns reflect international-standard teaching performance. The teacher’s speaking performance patterns are the embodiment of an activity related to the participants’ backgrounds. Good performance has a positive impact on learning. Performance is related to participants’ speech and indexicality. The speech describes the background and produces accompanying meanings. The differences in how they understand something.  This study aims to determine teacher performance in teaching at Prime One School. This study uses an anthropological approach because teacher performance patterns are related to participants and indexicality. This study uses a qualitative paradigm with an interactive model. The research data are teachers’ utterances. The data collection methods: direct pastoral observations and open and in-depth interviews. The interactive model is a data analysis method that consists of three stages: data condensation, data display, and verification/conclusion. This effectiveness is demonstrated by using structured language and appropriate intonation, which can attract students’ attention and increase their interest during the learning process. Teachers are also able to actively manage communication through questions and explanations, which can motivate students to be more involved in learning activities. This good speaking performance contributes positively to the achievement of learning objectives and creates a conducive learning environment. This research will contribute to teachers' understanding of their performance patterns during teaching.